The implementation of social customer relationship management for tourism information system - Ali Ibrahim; Dwi Rosa Indah; Devi Indra Meytri (Institute of Advanced Engineering and Science, 2021)
Semambu island village, Ogan Ilir regency, south Sumatra has been used as an agricultural and livestock education tour destination since November 2017 and there has been no customer data management since then. The use of social media as a promotional tool has not been done to its maximum potential. This can be seen from 189 people who liked its Facebook page or 11.05% out of the reached users, 192 followers or 11.23% and those who interacted as many as 114 people or 6.67% from the total users. Meanwhile, there were 709 followers on its Instagram which consisted of 48% men and 52% women at the time of the study. This research applied social customer relationship management (social CRM) in a website-based system. The waterfall model development method supported the customer relations management by utilizing Facebook and Instagram to improve customer relationships in providing travel information, knowing interest and listening to complains as well as their suggestions based on interactions with the social media users as existing and prospective customers.